Determinants The Quality of OPD Financial Statements (Empirical Study on OPD in Madura) - Noer Panca Mutawwab; Mohamad Djasuli; Muhammad Syam Kusufi (AFEBI Accounting Review, 2017)
There are still problems in the implementation of financial management, BPK finds as many as 10,154 and 15,434 issues containing the problems. In the acquisition of local government; The Local Government Financial Statements (LKPD) opinion Madura at year 2011-2015, only Pamekasan government increased, while Sampang and Sumenep consistently obtain Fair With Exceptions (WDP), and Bangkalan occurred a fall of LKPD opinion from Fair unqualified (WTP) to WDP. The objects of research are both the general chief  and employees / financial section staff / accounting, treasurer and the author of financial statement in the Organization of Local Government (OPD) of Local Government in Madura. The used research method is quantitative method, while the sampling technique in this study is purposive sampling technique. The results of this research are the government apparatus competence has a positive effect on the quality of OPD financial statement, the internal control system of government has a positive effect on the quality of OPD financial statement, the implementation of regional financial accounting system has a positive effect on the quality of OPD financial statement, the implementation of government accounting standards has a positive effect on the quality of OPD financial statement, ethic has a positive effect on  the quality of OPD financial statement, experience has a positive effect on the quality of OPD financial statement. Keywords: quality of financial statement, the Organization of Local Government (OPD)